2021
DOI: 10.1098/rsos.202108
|View full text |Cite
|
Sign up to set email alerts
|

Contours of citizen science: a vignette study

Abstract: Citizen science has expanded rapidly over the past decades. Yet, defining citizen science and its boundaries remained a challenge, and this is reflected in the literature—for example in the proliferation of typologies and definitions. There is a need for identifying areas of agreement and disagreement within the citizen science practitioners community on what should be considered as citizen science activity. This paper describes the development and results of a survey that examined this issue, through the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 39 publications
0
45
0
1
Order By: Relevance
“…However, we would like to express the notion that, as science opens up, the willingness of citizens to participate in accompanying research may decrease further. If citizens experience that they are emancipating themselves from being a science object to becoming a self-determined participant [2,3], they may increasingly want to question accompanying research. Experimental studies that turn respondents back into mere objects and leave them in the dark as to what the real research questions are will possibly be rejected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we would like to express the notion that, as science opens up, the willingness of citizens to participate in accompanying research may decrease further. If citizens experience that they are emancipating themselves from being a science object to becoming a self-determined participant [2,3], they may increasingly want to question accompanying research. Experimental studies that turn respondents back into mere objects and leave them in the dark as to what the real research questions are will possibly be rejected.…”
Section: Discussionmentioning
confidence: 99%
“…They thus focused on the process of scientific research and suggested possible roles and or activities for citizen scientists, which are often used to name the respective project type. The development of the ECSA characteristics of citizen science by Haklay et al [3] shows a very promising new approach. The characteristics were developed through the involvement of the interested community in citizen science.…”
Section: Level and Quality Of Participation In Citizen Science Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardoso et al (2011) recognized the role of citizen science as part of the solution for the scarce and underfunded science on invertebrates, including the declining number of insect taxonomists. There are various typologies of citizen science and viewpoints on what is or is not citizen science (Haklay et al, 2021). Here, we focus on volunteers and their contributions to field-based observations in a coordinated effort involving professional scientists (Bonney, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Citizen science projects are often categorized by their participation structure through a framework that groups projects by the degree of participation of citizens. Models of participation include contributory, with citizens volunteering data by participating in a project designed by scientists to advance scientific research; collaborative, on a project designed by scientists with citizen input; co-created, as a partnership of active engagement in all part of the project; contractual, in which researchers investigate on the behalf of citizens; and collegial, which are independent projects by non-institutional, often non-credentialed citizens [8][9][10][11][12]. Collegial projects can be specified as citizens involved in knowledge production to answer scientific questions as opposed to institutional researchers [13].…”
Section: Introductionmentioning
confidence: 99%